Boosting Toean Watiman Visitor Interest in 2023 through Instagram Promotion by @toean_watiman - Ekasaputri, Muthi Rabbani; Sari, Sovia Sitta (Universitas Muhammadiyah Surakarta, 2023)
This research aims to explore the use of Instagram social media by the Toean Watiman restaurant in increasing visitor interest. The restaurant uses the Instagram account @toean_watiman as a promotional tool to attract consumer attention. With the rapid growth of social media use in Indonesia, this research is relevant for understanding digital marketing strategies in the culinary industry. This research uses a qualitative description method with AISAS Attention model analysis. Consumers first see the product, followed by Interest, namely interest in the product, consumers look for information which is called Search, consumers make a purchase which is called Action, the information is shared with other people which is called Sharing. Data collection techniques use interview techniques, documentation techniques. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research show that the Toean Watiman restaurant uses Instagram as the main social media as a place to provide information, invite target consumers to buy products, and also provide warnings about holidays and new menus. This research is expected to provide deeper insight and insight into how the use of Instagram social media influences target consumers to buy products from Toean Watiman. This makes it possible to encourage the desire of target consumers to buy products from Toean Watiman, and is expected to persuade the local community as well. This research is expected to provide deeper insight and insight into how the use of Instagram social media influences the intended consumer target. By applying the concept of AISAS theory, it is hoped that it can increase the number of visitors that exceed the predetermined target each year. It is also hoped that this research can be a reference in utilizing promotions via Instagram social media.